Taxonomy of the genus Calamotropha Zeller (Lepidoptera: Crambidae: Crambinae) from China - Kim, Yongnam; Qi, Mujie; Wang, Shuxia; Li, Houhun (Zootaxa, 2023)
Thirty species of the genus Calamotropha Zeller, 1863 from China are reviewed. Five species are described as new: C. bleszynskii Kim & Li, sp. nov., C. duovirgata Kim & Li, sp. nov., C. nigerifera Kim & Li, sp. nov., C. parallela Kim & Li, sp. nov. and C. parvispina Kim & Li, sp. nov.; two species are newly recorded for China: C. alcesta Bleszynski, 1961 and C. punctivenella (Hampson, 1896). The female of C. sperlingi Li, 2019 is described for the first time. Calamotropha multicornuella Chen & Song, 2002 syn. nov. is synonymized with C. sienkiewiczi Bleszynski, 1961, and C. sawtoothella Chen & Song, 2002 syn. nov. is synonymized with C. latella (Snellen, 1890). Images of adults and genitalia of 28 known species with available specimens are provided, except images of genitalia provided by Li & Li in 2012. A key to the known Calamotropha species in China is included.